Prostat cancer profile in Dr. Sardjito General Hospital Yogyakarta - Yurisal Akhmad Dany; Ahmad Zulfan Hendri; Indrawarman Soerohardjo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2021)
Prostate cancer is the fourth most common type of non-skin malignancy in male malignancies. In Indonesia, the definitive data are unreported, however, Globocan reported prostate cancer in 5th place in 2018. Early diagnosis and treatment of this cancer are associated with reduced mortality rates. This study aimed to investigate the profile of prostate cancer in Dr. Sardjito General Hospital, Yogyakarta, Indonesia. A retrospective study involving a total of 90 prostate cancer patients who underwent follow-up care at Dr. Sardjito General Hospital, Yogyakarta in the period of 2015 to 2020 was conducted. Data of the patients from their medical records consisted of age, gender, prostate volume, PSA level, testosterone level, hydronephrosis, TURP history, histopathology results, Gleason scores, ISUP grade, and staging TNM were collected. The average of patients age was 67 ±10.4 y.o. where 22 (24.4%) patients aged < 60 y.o., 34 (37.8%) patients aged 61-70 y.o. and 34 (37.8%) patients aged >70 y.o. Almost of all patients (87 patients or 97.8%) were diagnosed as adenocarcinoma. Most of patients (73 patients or 81.4%) had prostate volume (TAUS) > 30 cm3 with the median at diagnosis was 51 cm3 (38.3 – 104.4). Furthermore, the median of PSA for diagnosis was 234.4 (94.4 – 1720.3) ng/mL and the median of testosterone level at diagnosis was 317 (10 - 384) ng/dL. In conclusion, most patients with prostate cancer are identified as adenocarcinoma with metastatic stage. In general, the prostate cancer patients age more than 61 years old with prostate volume (TAUS) > 30 cm3. In addition, prostate volume and testosterone level can be routinely used as initial screening and periodic assessment to evaluate prognosis and disease progression.